2000
DOI: 10.1159/000020655
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Modifications of Human Mesangial Cells by Extracellular Matrix: The Importance of Matrix in the Contractile Response to Reactive Oxygen Species

Abstract: The progression of chronic renal diseases is characterized by the accumulation of extracellular matrix proteins in the glomerulus. The present experiments were designed to analyze the effect of hydrogen peroxide on the contractile and proliferative phenotypes of human mesangial cells grown on different culture substrates: plastic, collagen type I, and collagen type IV. Contraction was analyzed by measuring planar cell surface area and myosin light chain phosphorylation, whereas proliferation was studied by [ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Multiple studies have analyzed the relationships among ECM proteins and cell morphology, proliferation, and apoptosis (3,11,12,16,24,26,31). However, the effect of ECM composition on cytokine synthesis has been poorly explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have analyzed the relationships among ECM proteins and cell morphology, proliferation, and apoptosis (3,11,12,16,24,26,31). However, the effect of ECM composition on cytokine synthesis has been poorly explored.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsinized HMC were seeded (4 ϫ 10 4 cells/cm 2 ) on petri dishes previously treated for 16 h at 4°C with a solution of COL I or COL IV (Sigma) (16). Briefly, culture dishes were coated with 12.5 g/ml COL I or COL IV in bicarbonate buffer (15 mM Na 2CO3 and 35 mM NaHCO3, pH 9) to form a thin film of collagen.…”
Section: Methodsmentioning
confidence: 99%
“…Acid soluble COL I and COL IV were purchased from Sigma (St. Louis, MO). Petri dishes were treated with a solution of 12.5 µg/ml collagen in bicarbonate buffer (Na 2 CO 3 15 mM, NaHCO 3 35 mM, pH 9) for 16 hours at 4° C to allow the formation of a thin film of collagen as previously described [20]. Then, the collagen not attached to plastic was discarded and Petri dishes were washed with Hank's balanced solution to restore the pH 7.5.…”
Section: Collagen Coating Platesmentioning
confidence: 99%
“…There is sufficient evidence that the trauma produced by skin wounds is responsible for the formation of free radicals, important pathogenic factors that lead to several degenerative disorders including fibrosis in different organs (e.g. the liver, lungs and skin) [Polosukhin, 1999;Iglesias-de La Cruz et al, 2000]. After analyzing the results, it was observed that the application of the ointment, especially at the higher dose, promoted an increase in the number of fibroblasts, which indicates that these cells retained the machinery for replication and synthesis of extracellular matrix components, particularly collagen fibers.…”
Section: Discussionmentioning
confidence: 99%